Case Report: Type 2 Diabetes Mellitus with Oral Abscess and Obesity I - Fatkurochman Fatkurochman; Aghnaa Gayatri (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Patient Mrs. L, a 62 y.o woman, private job, Javanese, address Kalikangkung Village RT/RW 03/06, Pangkah Subdistrict, Tegal Regency came to the Nusa Penida I Puskesmas to check blood sugar levels due to dentist referral with a molar tooth abscess 1 above right. The patient's right cheek is swollen for 2 days, pain when chewing and radiating to the right ear. Pulsating pain in the right upper jaw. The patient feels a foul smell coming from the oral cavity. The patient feels fever and headache. The maxillary teeth are sensitive to cold or heat for 2 weeks when eating hot or cold foods feels like the pain is electrocuted to the right temple. Previously the patient had never checked his blood sugar level.